2008
DOI: 10.1061/(asce)1076-0342(2008)14:3(214)
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Life-Cycle Assessment and Life-Cycle Cost Analysis Model for Concrete Bridge Deck Applications

Abstract: An integrated life-cycle assessment and life-cycle cost analysis model was developed and applied to enhance the sustainability of concrete bridge infrastructure. The objective of this model is to compare alternative bridge deck designs from a sustainability perspective that accounts for total life-cycle costs including agency, user, and environmental costs. A conventional concrete bridge deck and an alternative engineered cementitious composite link slab design are examined. Despite higher initial costs and gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(60 citation statements)
references
References 14 publications
(4 reference statements)
0
53
0
1
Order By: Relevance
“…Energy use and emissions arising from construction, operation and maintenance of the transport system infrastructures, in addition to the WTW and CTG stages, were included in the authors' analysis. For road transportation, these infrastructures dealt mostly with roadway construction, operation and maintenance, which can also be found in [17] LCA and parking lots. For on-road transportation, the authors found that the life cycle component contributions are roughly the same as the GHG contributions and produce 1.4e1.6 times larger life cycle factors than the operational components.…”
Section: Introductionmentioning
confidence: 99%
“…Energy use and emissions arising from construction, operation and maintenance of the transport system infrastructures, in addition to the WTW and CTG stages, were included in the authors' analysis. For road transportation, these infrastructures dealt mostly with roadway construction, operation and maintenance, which can also be found in [17] LCA and parking lots. For on-road transportation, the authors found that the life cycle component contributions are roughly the same as the GHG contributions and produce 1.4e1.6 times larger life cycle factors than the operational components.…”
Section: Introductionmentioning
confidence: 99%
“…This is quite similar to predictor-corrector cycles. The life assessment discussed in this paper is expected to be involved in life cycle cost assessment (Kendall et al 2008;Biondini et al 2006).…”
Section: Assimilation With Aetmentioning
confidence: 99%
“…The research on the unit pollution damage cost is still very weak, making it difficult to convert all of the environmental impacts into an environmental cost. Kendall et al [26] provided pollution damage cost estimates, and these cost estimates were adjusted to 2003 United States dollars, as shown in Table 1. According to the WTP method, Li et al put forward the carbon emission and energy damage costs of China, with 0.22 Yuan/kg CO 2 -e and 3.79 × 10 −3 Yuan/kgce, respectively [27].…”
Section: Monetary Valuation Of the Environmental Impact (Environmentamentioning
confidence: 99%